Distraction osteogenesis of mandible: our experience at RIMS, Ranchi - Priya, Astha; Prakash, Om; Kumar, Sandeep; Mark, Rajiv Romal; Dubey, Ujjwal Kumar; Kumar, Piyush (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Distraction osteogenesis has become an important modality in management of craniofacial deformities particularly in mandibular hypoplasia. This article describes extraoral distraction osteogenesis of mandible in management of mandibular deformities in 08 cases. Majority of patients presenting with mandibular deformities were secondary to TMJ ankylosis with a history of trauma. Body of mandible was primarily involved in 63% patients while in 37% patient’s ramus of mandible was involved. Bilateral distraction device placement was done in 05 (62%) cases and unilateral distraction device placed in 03 (38%) cases. Sliding genioplasty was performed additionally in severe mandibular hypoplasia (37.5% cases) to achieve a good profile. 63% patients were satisfied with the improved facial features both frontal and profile with functional harmonious occlusion noted while 37% patients were not satisfied as there was not significant improvement in facial symmetry. Distraction osteogenesis is a valuable tool for mandibular reconstruction, though individualized planning and careful execution are critical to minimize complications and optimize results. Multidisciplinary approach plays a key role in patient management and satisfaction assessment.